The role of in utero endotoxin exposure in the development of inflammatory bowel disease in mice. (4th August 2020) - Banfield, Emilyn; Fulton, William; Burd, Irina; Kovler, Mark L.; Sodhi, Chhinder P.; Hackam, David J.
Abstract: Problem: Although early environmental influences are thought to influence the development of inflammatory bowel disease (IBD), little is known about the role of the in utero environment on subsequent IBD risk. We hypothesized that prenatal exposure to bacterial lipopolysaccharide (LPS) could modify the subsequent development of dextran sulfate sodium (DSS)‐induced ulcerative colitis in adulthood by influencing the associated cellular and immune response. Method of Study: To test this hypothesis, we exposed developing mice in utero to LPS or saline (PBS) at E17.5, and then induced colitis at 5 weeks. We then assessed colitis severity and effects on the microbiome. In order to define the developmental impact of any potential LPS effect, we also exposed 1‐week‐old mice to either LPS or saline before inducing colitis at 5 weeks. Results: Mice that had been exposed to LPS but not saline in utero were protected from subsequent colitis development, and their intestinal barrier integrity and tight junction expression distribution were similar to that of control mice that were not exposed to DSS. By contrast, mice exposed to either LPS or saline at day 7 of life all developed severe colitis upon subsequent DSS exposure. Conclusion: These results identify an informative time window during fetal development during which exposure to an otherwise pro‐inflammatory agent like LPS protects against an inflammatory disease in adulthood. Abstract : The role of in utero endotoxin exposure in the development of inflammatory bowel disease in mice.